Between Culture and the Sacredness of Fiqh: The Role of Lebe in Child Marriage Practices in Brebes, Indonesia - Millati Agustina, Arifah (Journal of Islamic Law, 2022)
This article analyses the role of lebe (penghulu or local marriage officiant) in the practice of child marriage in Brebes, Indonesia. Ranked second after Indramayu, Brebes is a district that still has a Sundanese cultural heritage with its deep-rooted practice of child marriage. The fundamental question in this article is, what is the role of lebe in the practice of child marriage in Brebes? Is child marriage in Brebes a generic culture from its predecessors, or is this culture a form of cultural appropriation (perpetuating a culture that is not its own because of cultural domination)? Using a socio-legal research framework, the author argues that lebe plays a vital role in rooting the practice of child marriage in Brebes. His understanding of classical fiqh (Islamic jurisprudence) as a dogma legitimizes the practice of child marriage in Brebes. He prioritizes aspects of the readiness of the bride and groom rather than the minimum age limit for marriage regulated by the state. Besides the role of lebe, the understanding of the community who views that the age of marriage is relative, women must be protected, the culture of child marriage as a stepping stone to a better life, and the cultural war between populists (community) and elitists (village government officials), distrust of education is another factor that perpetuates the practice of child marriage in Brebes.